Digitalization as a way to promote the holistic approach to faculty development: a developmental evaluation - Silva, Roberta (Frontiers in Education, 2023)
Faculty Development, in the last decades, has undergone many transformations and many scholars are now wondering what will be the main feature that will characterize the next age, an age distinguished, in the academic world, by the changes that the just experienced pandemic brought with it. One of the main changes that this pandemic has brought with itself is the increase in digitalization within academic institutions and, consequently, the increase in the number of faculty development proposals that are conveyed through online initiatives. However, this is a consideration that can be read not only as a stand-alone element but also, if properly contextualized, it could be used as a way to promote Faculty Development programs that exploit the potential offered by digitalization in order to create initiatives which are linked in a mutually reinforcing bond. This choice is consistent with the adherence to a holistic approach to Faculty Development that promotes a systemic and multifocal logic. This paper presents a study conducted at the University of Verona in order to discover if the Faculty Development programs here implemented applying this approach were been able to promote a reciprocal mirroring between them. In order to answer this question, it was considered useful to investigate the results of a survey carried out on the “Competenze Trasversali” program, in its first edition, and thus still in an “experimental” phase. In order to collect the data has been used a simplified version of SWOT Analysis was used and the answers to the open questions were analyzed using the content analysis.